SOSIALISASI DAN PELATIHAN WEBSITE DESA SIDODADI BAGI APARATUR PEKON DAN KARANG TARUNA - Rinawati Rinawati; Kasmi Kasmi; Yuri Fitrian (LP3K Lampung, 2022)
The website is the fastest and widest medium for conveying information. Websites can provide various information regarding company profiles, educational institution profiles, community profiles, organizational activities, government business entities, knowledge-sharing media, and others. Websites can not only be used by large companies or institutions but are widely used by village administrations as promotional media that are economical while at the same time displaying professionalism so that the website becomes one of the most reliable media. Aside from being a medium for village promotion, the Sidodadi village website also displays Village Profiles, Population Data for the Sidodadi community, the History of Pekon Sidodadi, and the Potential of Sidodadi Village. The Sidodadi Village community is engaged in rice field farming, agricultural product management, and Sidodadi community handicrafts. BUMDes Desa Sidodadi itself does not yet have a system or online media by utilizing internet facilities to expand the reach of promotions in introducing agricultural products and handicrafts from the Sidodadi community, services, or business potential profiles to consumers or the general public at large. Therefore, in this service, the Computer Systems study program carries out community service activities by introducing and building a Sidodadi Village website that can be managed properly and is friendly and can be accessed online by utilizing adequate internet facilities.